2006
DOI: 10.1589/jpts.18.107
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic Strength and Functional Status in Knee Osteoarthritis

Abstract: Abstract. Muscle function and functional performance are affected in patients with osteoarthritis (OA). The aim of the study was to investigate and compare the concentric torque of knee muscles (quadriceps and hamstring) and functional status in two matched groups: one group of patients with low grade of tibiofemoral OA, and one group of matched healthy subjects. Concentric peak torques of quadriceps and hamstring were measured in both groups at an angular velocity of 90 and 150 degree/second. In addition, sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
(33 reference statements)
1
21
0
3
Order By: Relevance
“…Adding the isokinetic strength training to the rehabilitation program provides the best way for improving muscle strength aiming to increase the motor performance of the affected lower limb. This comes in agreement with Emrani et al [41] who reported that strength training can be applied in different modes which work differently through the range of motion. During traditional isotonic strength training, the weakest mechanical points of the range of motion are subjected to greatest load, while the rest of the angles work at less than maximal capacity.…”
Section: Results and Tablessupporting
confidence: 92%
“…Adding the isokinetic strength training to the rehabilitation program provides the best way for improving muscle strength aiming to increase the motor performance of the affected lower limb. This comes in agreement with Emrani et al [41] who reported that strength training can be applied in different modes which work differently through the range of motion. During traditional isotonic strength training, the weakest mechanical points of the range of motion are subjected to greatest load, while the rest of the angles work at less than maximal capacity.…”
Section: Results and Tablessupporting
confidence: 92%
“…Upper leg muscle strength is reported to be approximately 20-40% lower compared with healthy age-matched controls (1,3). Muscle weakness in knee or hip OA is strongly related to the patient-reported outcomes pain, activity limitations and falls, and has been linked to symptomatic progression of the disease (2,(4)(5)(6)(7)(8). Moreover, muscle weakness has been reported to be a risk factor for radiographic progression and the development of knee OA (9,10).…”
mentioning
confidence: 99%
“…Emrani and colleagues found that significant decreases in isokinetic torques and longer walking times in patients with knee osteoarthritis were observed compared to healthy controls. They thought that because of muscle weakness, the patients may change in their gait pattern and also their walking pace was slowed down [17]. Similarly, one recent study pointed out that quadriceps strength in both sexes was one of the strong predictors of speedrelated gait variables [18].…”
Section: Discussionmentioning
confidence: 99%